1994
DOI: 10.1021/bi00200a006
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a DNA Duplex Containing 8-Hydroxydeoxyguanine-Adenine Base Pairs

Abstract: The crystal structure of the oligonucleotide d(CGCAAATTO8GGCG), containing the chemically modified base 8-hydroxydeoxyguanine (O8G), has been determined at 2.5-A resolution and refined to a crystallographic R-factor of 16.8%. The B-type DNA helix contains standard Watson-Crick base pairs except at the mismatch sites, where O8G adopts a syn conformation and forms hydrogen bonds to adenine in the anti conformation. The thermodynamic stability of the duplex was found by UV melting techniques to be intermediate be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
232
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(240 citation statements)
references
References 28 publications
8
232
0
Order By: Relevance
“…These results are consistent with previous thermodynamic results as well as NMR and X-ray crystal structure studies (50)(51)(52), which showed that 8-oxodG can form base pairs with both dC and dA, depending on whether the damaged nucleoside adopts an anti or syn configuration about the glycosidic bond (50,51).…”
Section: Thermodynamic Studiessupporting
confidence: 93%
“…These results are consistent with previous thermodynamic results as well as NMR and X-ray crystal structure studies (50)(51)(52), which showed that 8-oxodG can form base pairs with both dC and dA, depending on whether the damaged nucleoside adopts an anti or syn configuration about the glycosidic bond (50,51).…”
Section: Thermodynamic Studiessupporting
confidence: 93%
“…2, a and b); conversely, the same lesion is recognized by hOgg1 in the anti glycosidic configuration (15). The syn configuration is thermodynamically favored over anti for an isolated oxoG nucleoside (26), but both rotamers are found in oxoG-containing duplex DNA, with syn being preferred for oxoG paired opposite A (27,28) and anti being preferred for oxoG opposite C (29,30). The ␤F-␣10 loop plays a key role in recognition of the oxoG base.…”
Section: Resultsmentioning
confidence: 99%
“…The ⅐OH are believed to arise via the metal (e.g., Fe ϩ2 )-catalyzed decomposition of H 2 O 2 , such as in redox cycling of hormones (5) and xenobiotics (6). The 8-oxo lesions contribute to localized conformational changes in base pairing and vertical base stacking within the DNA helix, as suggested by x-ray diffraction studies (7)(8)(9)). …”
mentioning
confidence: 99%
“…Accordingly, it has been suggested that nucleotide-localized changes probably lead to alterations in the fidelity of DNA repair (8,11) and create synthesis errors at the replication fork (2,8,10). Until recently, almost no information existed on whether the radical-induced changes in base structure also give rise to conformational alterations in the phospho-deoxyribose backbone.…”
mentioning
confidence: 99%